PENINGKATKAN KETERAMPILAN MENGENDALIKAN VARIABEL DAN MENDEFINISIKAN VARIABEL SECARA OPERASIONAL MELALUI PEMBELAJARAN LEARNING CYCLE 3E - Dhita Mita Anggra Ovika; Noor Fadiawati; Chansyanah Diawati (Universitas Lampung, 2013)
The aimed this study was to describe the increase of students’ skill in controlling variables and defining variables operationally on Learning Cycle three-phase (LC-3E). The model was applied pretest-posttest control group design. The participants included two clsses at the second year sains of SMA N 1 Way Jepara, Lampung Timur. The increase of students’ skill in controlling variables and defining variables operationally measured on the difference of a significant normalized gain (n-Gain). The results show that mean value of n-Gain controlling variables skill in control and experimental classes were 0.15 and 0.47, and the mean value of n-Gain defining variables operationally skill in control and experimental classes were 0.23 and 0 , 50. Based on hypothesis testing using t-test and n-Gain, it was concluded that the LC 3E learning model can increasing students’ skill in controlling variables and defining variable operationally.Kata kunci: Learning Cycle 3E, keterampilan mengendalikan variabel, dan mendefinisikan variabel secara operasional